2019
DOI: 10.1136/bcr-2018-226064
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of stage III hidradenitis suppurativa with botulinum toxin A

Abstract: A 41-year-old obese Native American woman presented with hidradenitis suppurativa (HS) after failing all available treatment options. Her HS was more pronounced in the axillary and groin regions (Hurley stage III) and was a major source of her pain and a barrier for home exercise and aquatic therapy. She received a botulinum toxin A injection every 3 months (four times thus far), which has significantly helped alleviate her pain and curb the progress of her HS by resolving abscesses and healing draining sinuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…Given the apocrine distribution of HS, we hypothesized that hyperhidrosis could be a comorbidity that contributes to disease activity and morbidity. This hypothesis was supported by 5 case reports [1][2][3][4][5] demonstrating the excellent response of HS in 6 patients (of whom 3 demonstrated clinical remission) who were treated with botulinum toxin A (BoNT-A), a treatment for hyperhidrosis approved by the U.S. Food and Drug Administration. Half of these patients presented with hyperhidrosis or increased sweat production.…”
Section: Hyperhidrosis Affects Quality Of Life In Hidradenitis Suppurmentioning
confidence: 88%
See 1 more Smart Citation
“…Given the apocrine distribution of HS, we hypothesized that hyperhidrosis could be a comorbidity that contributes to disease activity and morbidity. This hypothesis was supported by 5 case reports [1][2][3][4][5] demonstrating the excellent response of HS in 6 patients (of whom 3 demonstrated clinical remission) who were treated with botulinum toxin A (BoNT-A), a treatment for hyperhidrosis approved by the U.S. Food and Drug Administration. Half of these patients presented with hyperhidrosis or increased sweat production.…”
Section: Hyperhidrosis Affects Quality Of Life In Hidradenitis Suppurmentioning
confidence: 88%
“…We therefore sought to confirm the efficacious treatment of HS by BoNT-A, as demonstrated by the 5 case reports. [1][2][3][4][5] To investigate this, we conducted a prospective analysis to assess the effectiveness of one-time treatment of BoNT-A (100 units, 2.5 units per 1.5 cm) in 5 patients with HS at the Stanford Department of Dermatology. All patients were female and endorsed excessive sweating, with an average age of 38.6 years and Hurley stages I to III.…”
Section: Hyperhidrosis Affects Quality Of Life In Hidradenitis Suppurmentioning
confidence: 99%
“… 54 A study by Feito-Rodriguez et al 55 reported that the BoNT-A was successfully treated the prepubertal HS in 6-year-old girl. A case report by Shi et al 56 observed that the BoNT-A was successfully treated the stage −3 HS in 41-year-old female. Recently, a study by Grimstad et al 57 assessed whether intradermal injection with BoNT-B is an effective treatment for HS among 20 patients.…”
Section: Role Of Bont In Dermatologymentioning
confidence: 99%
“…More recently, several case reports and case series have been published on this topic. Shi et al [154] have described the use of BoNT-A in a 41-year-old obese Native American woman affected by a HS localized in the axillary and groin regions (Hurley stage III) resistant to all available therapies. She received an injection every 3 months (four times thus far), which had significantly helped alleviate her pain and curbed the progress of her HS by resolving abscesses and healing draining sinuses.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%